Sensitivity and specificity of autoantibodies against CD74 in nonradiographic axial spondyloarthritis - Riechers, Elke; Baerlecken, Niklas; Baraliakos, Xenofon; Bakhsh, Katrin Achilles-Mehr; Aries, Peer; Bannert, Bettina; Becker, Klaus; Brandt-Jürgens, Jan; Braun, Jürgen; Ehrenstein, Boris; Euler, Hans-Hartwig; Fleck, Martin; et al. (Arthritis & rheumatology, 2019)
Objective Autoantibodies against CD74 (anti-CD74) are associated with ankylosing spondylitis (AS). The present multicenter study, the International Spondyloarthritis Autoantibody (InterSpA) trial, was undertaken to compare the sensitivity and specificity of anti-CD74 and HLA-B27 in identifying patients with nonradiographic axial spondyloarthritis (axSpA). Methods Patients ages 18-45 years with inflammatory back pain of ≤2 years’ duration and a clinical suspicion of axSpA were recruited. HLA-B27 genotyping and magnetic resonance imaging of sacroiliac joints were performed in all patients. One hundred forty-nine patients with chronic inflammatory back pain (IBP) not caused by axSpA served as controls, and additional controls included 50 AS patients and 100 blood donors whose specimens were analyzed. Results One hundred patients with inflammatory back pain received a diagnosis of nonradiographic axSpA from the investigators and fulfilled the Assessment of SpondyloArthritis international Society (ASAS) criteria. The mean age was 29 years, and the mean symptom duration was 12.5 months. The sensitivity of IgA anti-CD74 and IgG anti-CD74 for identifying the 100 axSpA patients was 47% and 17%, respectively. The specificity of both IgA anti-CD74 and IgG anti-CD74 was 95.3%. The sensitivity of HLA-B27 was 81%. The positive likelihood ratios were 10.0 (IgA anti-CD74), 3.6 (IgG anti-CD74), and 8.1 (HLA-B27). Assuming a 5% pretest probability of axSpA in chronic back pain patients, the posttest probability, after consideration of the respective positive test results, was 33.3% for IgA anti-CD74, 15.3% for IgG anti-CD74, and 28.8% for HLA-B27. A combination of IgA anti-CD74 and HLA-B27 results in a posttest probability of 80.2%. Conclusion IgA anti-CD74 may be a useful tool for identifying axSpA. The diagnostic value of the test in daily practice requires further confirmation.